Concept of Space as a Factor of Economic Development of the Polar Urals in 16th – Early 20th Century - Tatarkin A. I.; Sukhikh V. V.; Vazhenin S. G.; Vazhenina I. S. (Prostranstvennaâ Èkonomika, 2010)
The meaning of the concept of space is analyzed. The example of the Polar Urals is taken to show the importance of the concept of space in economic development of a region. The history of economic development of the Polar Urals in the 16th – early 20th century is analyzed